EU Trade Policy in Light of the New Industrial Strategy for Europe - Malorie Schaus (Intereconomics)
Abstract EU trade policy, which is essential to a prosperous European economy and industry, has an important role to play in tackling the major challenges of our times relating to worsening geo-economic and trade tensions, enduring global sustainability issues and a deteriorating multilateral order.